2014
DOI: 10.3109/14767058.2014.906572
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of systemic antibiotics during pregnancy in primary care in Friuli Venezia Giulia, Northeastern Italy

Abstract: In order to improve the prescription of antibiotics in pregnancy, an audit with the GPs is warranted to understand their motivations, discuss clinical cases and build consensus guidelines on which antibiotics should be preferred for use in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…The estimated rate of drug prescriptions in pregnancy among women delivering in Latium from 2008 to 2012 was 81% excluding vitamin and minerals. To our knowledge the only two other population-based studies conducted in 2004 and in 2011 in two regions of northern Italy [ 13 , 15 ] reported respectively 48,3 and 72,7% of antenatal prescriptions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The estimated rate of drug prescriptions in pregnancy among women delivering in Latium from 2008 to 2012 was 81% excluding vitamin and minerals. To our knowledge the only two other population-based studies conducted in 2004 and in 2011 in two regions of northern Italy [ 13 , 15 ] reported respectively 48,3 and 72,7% of antenatal prescriptions.…”
Section: Discussionmentioning
confidence: 93%
“…This proportion is higher compared to other population-based studies in European settings ranging from 27 to 32% [ 20 22 ] and similar to a French study where 42% of pregnant women were exposed to antimicrobials [ 23 ]. The previous Italian studies reported respectively 37.2 and 24.8% of women prescribed with antibiotics during pregnancy [ 13 , 15 ]. Given the growing problem of bacterial resistance, an increase in the use of antibiotics during pregnancy requires careful thought in terms of prescriptive appropriateness [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, as before ( 44 ), and recognizing the issues of antimicrobial resistance, one avenue would exploit antibiotics much more commonly than now. We note that pharmaceutical drugs are prescribed or taken during 50% or more of pregnancies ( 819 828 ). Anti-infectives are the most common such drugs, and some 20–25% of women or more are prescribed one or more antibiotics during their pregnancies ( 820 , 821 , 824 , 826 , 828 832 ).…”
Section: Treatment Options Based On (Or Consistent With) the Ideas Prmentioning
confidence: 99%
“…Clearly, as before [32], and recognising the issues of antimicrobial resistance, one avenue would exploit antibiotics much more commonly than now. We note that pharmaceutical drugs are prescribed or taken during 50% or more of pregnancies [769][770][771][772][773][774][775][776][777][778]. Anti-infectives are the most common such drugs, and some 20-25% of women or more are prescribed one or more antibiotics during their pregnancies [770; 771; 774; 776; 777; 779-782].…”
Section: Treatment Options Based On (Or Consistent With) the Ideas Prmentioning
confidence: 99%